2018
DOI: 10.1002/adfm.201802847
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle‐mediated HMGA1 Silencing Promotes Lymphocyte Infiltration and Boosts Checkpoint Blockade Immunotherapy for Cancer

Abstract: For most cancer types, only a minority of cancer patients respond to checkpoint inhibition therapy. T lymphocyte infiltration is critically important for checkpoint blockade immunotherapy. High expression of high mobility group protein A1 (HMGA1) is observed in rapidly proliferating neoplastic cells, and is reported to contribute to the immunosuppressive microenvironment in the tumor. Herein, whether the silencing of HMGA1 using a nanoparticle (NP) approach could promote T lymphocyte infiltration into the tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 54 publications
0
35
0
Order By: Relevance
“…[152] A low dose of lmGem-LNC was sufficient to induce remarkable decrease of monocytic MDSCs both in the spleen and tumor. [153] In the highly metastatic colon cancer model, treatment with siHMGA1 NPs significantly increased the frequency of DCs and CD3+CD45+ T cells and reduced the number of MDSCs. Furthermore, injection of lmGem-LNCs 24 h before ACT treatment provided a more suitable microenvironment for T cell proliferation, which facilitated the activation of CD8+ T cells and drastically improved the survival rate of mice.…”
Section: Doi: 101002/advs201900101mentioning
confidence: 96%
See 1 more Smart Citation
“…[152] A low dose of lmGem-LNC was sufficient to induce remarkable decrease of monocytic MDSCs both in the spleen and tumor. [153] In the highly metastatic colon cancer model, treatment with siHMGA1 NPs significantly increased the frequency of DCs and CD3+CD45+ T cells and reduced the number of MDSCs. Furthermore, injection of lmGem-LNCs 24 h before ACT treatment provided a more suitable microenvironment for T cell proliferation, which facilitated the activation of CD8+ T cells and drastically improved the survival rate of mice.…”
Section: Doi: 101002/advs201900101mentioning
confidence: 96%
“…[67] To achieve precise and controlled drug delivery, smart nanoparticles with more complex structures and specific drug release properties are also being produced according to the hallmarks of TME, such as weak acidic pH (6.5-6.8), high level of glutathione and hydrogen peroxide (H 2 O 2 ), and disorder of proteinases production, such as matrix metalloproteinase-2 (MMP-2). HDL-mimicking nanodisc Patient-derived neoantigen and cholesterol-modified CpG -- [135] PLGA NP OVA, Pam3Csk4, and Poly(I:C) CD40 on DCs - [136] Chitosan nanoparticle Cell lysate from B16 melanoma Mannose receptor on DCs - [38] Lipo-CpG micelle CpG Albumin hitchhiking - [137] γPGA-based CNNP OVA and poly(I:C) -- [138] PLGA-based AC-NP --- [139] mBiNE CRT HER-2 on tumor cells - [140] T cell activation DMAEMA, PAA, and butyl methacrylate OVA -pH [134] polyPAA OVA -pH [133] CNT MHC1 peptide, anti-CD28, and PLGA NPs encapsulating IL-2 and magnetite -- [141] Magnetic nanocluster MHC1-OVA, anti-CD28, and leukocyte membrane fragments Magnetic navigation - [128] PD-1 receptor-expressing NV --- [142] PEG-PLA NP CTLA-4 siRNA -- [143] Platelet-derived microparticle Anti-PD-L1 Ab -- [144] PEG-PLGA NP Anti-PD-1 Ab and aOX40 -- [145] Super-paramagnetic iron oxide nanoparticle Anti-PD-L1 Ab, anti-CD3/anti-CD28 Ab, fucoidan, and dextran Magnetic navigation - [129] Regulation of TME PLGA NP core with lipid shell Imatinib Nrp1 receptor on Tregs - [43] CDNP consisting of CD and lysine R848 -- [146] NV derived from type 1 macrophage --- [147] Carboxyl-functionalied and aminofunctionalized polystyrene nanoparticle --- [148] Super-paramagnetic iron oxide --- [149] Ferumoxytol --- [150] HDL NP -Scavenger receptor B1 on MDSCs - [151] PEGylated LNC lmGem -- [152] LPH NP HMGA1 siRNA Sigma receptor on tumor cells - [153] LCP NP TGF-β siRNA, tumor antigen, and CpG -- [154] PEG-PLGA NP SD-208 PD-1 on T cells - [155] Nanoparticle assembled from DEAP molecule, PD-L1 antagonist, NGL919, and a substrate peptide of MMP-2 -pH and MMP-2 …”
Section: Doi: 101002/advs201900101mentioning
confidence: 99%
“…Starting in 2017, the Huang group published a series of papers using a similar particle design (i.e., a liposome‐protamine‐DNA (LPD) nanoparticle) to deliver genes for various anticancer purposes, including those that encode for proteins that bind to (or trap): i) the immunosuppressive proteins PD‐L1 and C‐X‐C motif chemokine (CXCL)12, ii) the signaling protein Wnt family member 5A (Wnt5a), which has been implicated in inducing dendritic cell tolerance, iii) IL‐10, which is known to suppress dendritic cells from releasing IL‐12, to develop Th1 responses, iv) LPS, which relieved the immunosuppressive microenvironment and boosted anti‐PD‐L1 therapy against colorectal tumors, and v) CCR‐7, which is associated with the metastasis of breast cancer . The group also investigated the delivery of siRNA to silence high mobility group protein A1 (HMGA1), which is associated with immunosuppression . Finally, in 2018, Sailor and co‐workers used positively charged fusogenic liposomes to augment immune responses to infection from Staphylococcus aureus ( Figure ) .…”
Section: Nanoscale Materials For Immunotherapymentioning
confidence: 99%
“…[161] The group also investigated the delivery of siRNA to silence high mobility group protein A1 (HMGA1), which is associated with immunosuppression. [162] Finally, in 2018, Sailor and co-workers used positively charged fusogenic liposomes to augment immune responses to infection from Staphylococcus aureus (Figure 4). [148] The authors showed that the delivery of siRNA could knockdown the proinflammatory marker IRF5 in macrophages to increase their clearance capability and accelerate healing.…”
Section: Cationic Liposomesmentioning
confidence: 99%
“…Ying et al delivered small‐interfering RNA (siRNA) of high mobility group protein A1 (siHMGA1) which was highly expressed in rapidly proliferating neoplastic cells and contributed to the immunosuppressive microenvironment in the tumor, by a LPH‐siHMGA1 NP system. Combined with PD‐L1 trap, the system significantly enhanced the lymphocyte infiltration in the tumor, inhibited tumor growth and prolonged survival (Y. Wang, Song, et al, ).…”
Section: Functional Nanomaterials For Delivering Immunomodulatory Drugsmentioning
confidence: 99%